1987
DOI: 10.1007/bf00145232
|View full text |Cite
|
Sign up to set email alerts
|

Basic research and clinical aspects of the oscillatory potentials of the electroretinogram

Abstract: This paper reviews current knowledge concerning the oscillatory potentials (OPs) of the electroretinogram (ERG). The first section describes the basic characteristics of the OPs primarily studied in healthy subjects. The behavior of the OPs is different from the a- and b-waves, indicating separate mechanisms for generation of the OPs compared with the major components of the ERG. The second section deals with the present view of the origin of the OPs collected from experimental studies of the vertebrate retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
1
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 42 publications
2
62
1
1
Order By: Relevance
“…In this study, we observed a diabetes-induced increase in OP latency, and topically applied Nepafenac inhibited the increased OP latency despite persistent hyperglycemia. It is widely accepted that the OPs primarily originate from the amacrine cell layer, although some have observed a possible ganglion cell contribution in certain species (46,47). More detailed analysis is needed to discern if Nepafenac treatment directly affects amacrine cell function in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a diabetes-induced increase in OP latency, and topically applied Nepafenac inhibited the increased OP latency despite persistent hyperglycemia. It is widely accepted that the OPs primarily originate from the amacrine cell layer, although some have observed a possible ganglion cell contribution in certain species (46,47). More detailed analysis is needed to discern if Nepafenac treatment directly affects amacrine cell function in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the OP score behavior, besides specifying a more sensitive ERG pa rameter to differentiate the two rat strains, could hypothetically imply that the structure responsible for OP generation is involved very early in the progressive retinal deteriora tion in the WAG/Rij rats. On the basis of experimental studies also performed on the primate retina, the generation of OPs could involve the bipolar, the amacrine and/or the interplexiform cells [9,10]. In any case, the OPs should represent the activity of inhibi tory feedback circuits of the inner plexiform layer.…”
Section: Discussionmentioning
confidence: 99%
“…1990. ing with the normal synaptic/nonsynaptic neural func tions at different retinal or brain structures/subsystems [Grant. 1974: François andDe Rouck, 1978;Shagass and Straumanis, 1978: Bodis-Wollner et al, 1982, 1986aWachtmeister, 1987;Sannita, 1991], The evidence de-rives from clinical experience as well as from experimen tal approaches ranging from humans to animals, to in vitro models. The available knowledge about the physiol ogy of the visual system and the basic pharmacology of the retina, as well as the possibility of attributing electrophysiological changes to functional subsystems by relying on the response to the physical characteristics of the stim ulus (e.g.…”
Section: Introductionmentioning
confidence: 99%